BAX 2016 : Best American Experimental Writing - Morris, Tracie; Bernstein, Charles, 1950- (Book collections on Project MUSE., 2017)
BAX 2016: Best American Experimental Writing is the third volume of this annual literary anthology compiling the best experimental writing in poetry, fiction, and creative nonfiction. This year's volume, guest-edited by Charles Bernstein and Tracie Morris, features seventy-five works by some of the most exciting American poets and writers today, including established authors--like Sina Queyras, Tan Lin, Christian Bök, Myung Mi Kim, Juliana Spahr, Samuel R. Delany, and even Barack Obama--as well as emerging voices. Intended to provoke lively conversation and debate, Best American Experimental Writing is an ideal literary anthology for contemporary classroom settings.